A Survey on Path Planning Techniques for Mobile Sink in IoT-Enabled Wireless Sensor Networks - Agarwal V.; Tapaswi S.; Chanak P. (My University, 2025)
Recently, the Internet of Things (IoT) had emerged very rapidly and became the most important technology in today’s era. In an IoT-based environment, every physical object is connected to the internet. It has many applications in the fields of home automation, healthcare, military, weather forecasting, and industrial monitoring. Wireless Sensor Networks (WSNs) acting as a backbone of any IoT-based system where IoT-enabled sensor nodes are deployed to collect real-time data from the monitoring environment. IoT-enabled WSNs require well-designed network architecture so that the overall lifetime of the network increases since the nodes are battery-operated. The overall performance of the architecture depends on how the data is transmitted from the source nodes to the Base Station efficiently and effectively by minimizing the data losses. Static Sinks and Mobile Sinks are used for data gathering in IoT-enabled WSNs. But the performance of Mobile Sink (MS) based data gathering approaches are more efficient as compared to Static Sink based data gathering approaches. However, MS-based data gathering approaches have several drawbacks and limitations. Therefore, a detailed study of the existing state-of-the-art MS-based data gathering approaches can help further development in this direction. In this paper, the working of the sensor network is explained with its application in various fields. It also discusses the various path selection algorithm used for the MS to gather the information in the shortest possible time by minimizing the energy dissipation of each node to enhance the overall lifetime of the whole network. Some other factors also affect the path planning for a MS which is discussed and explained in the paper. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.